PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN - Elita Rafini; Rima Rahmayanti (Jurnal Istiqro, 2025)
This research aims to determine the effect of workload and work stress on the performance of Pratama Medika Stania Clinic employees in Belinyu City, Bangka Regency, Bangka Belitung Province. This research is quantitative, and the analysis unit is the Pratama Medika Stania Clinic Employees. Data was collected by distributing questionnaires to 25 employees. The results of hypothesis testing state that workload has a partial effect on employee performance, and work stress has a partial effect on employee performance. Additionally, workload and work stress simultaneously positively and significantly affect employee performance. So, the results of hypothesis testing have a positive influence both partially and simultaneously.